Rare Association of Pneumomediastinum With Bilateral Pneumothorax - Saleem, Noman (Cureus, 2020)
Pneumomediastinum with bilateral pneumothorax is a clinical entity caused by infections, malignancy, or trauma, as in our case. Some patients present with pneumomediastinum secondary to trauma have esophageal, laryngeal, or tracheal injuries. A 16-year-old boy presented in the emergency department with complaints of shortness of breath and bruise on the chest after a history of the road traffic accident. Bilateral chest tube thoracotomy was done. Pneumomediastinum was suspected on X-ray chest and confirmed on computed tomography of the chest, which showed bilateral pneumothorax with pneumomediastinum. The patient was conservatively managed and discharged after 10 days.